The dynamics of task performance among boys during their second year of studying at educational establishment - Клюс [Elena Klyus] Олена Анатоліївна (Slobozhanskyi Herald of Science and Sport, 2013)
Thefindings of one-year ascertaining experiment have been analyzed in the article that show the display and change of task performance among seven-year old boys on different days of an academic week and periods of the academic year. It has been determined that such task performance as for the volume and speed processing of visual information during every day of the first and the last academic weeks of both terms is marked with a similar tendency for change and peculiarities of the display which are connected with a period of the academic year and a day of an academic week. The possibility of task performance maintenance among the boys during a week at the achieved level without their health hazard has been stated only under the condition of improvement of the activity and the content of physical education that is implemented during a working day in various forms.